The choice explosion: human lives, human genes, human numbers - Anderson, Walter Truett (Array, 2009)
Today, people all over the world are swimming (and sometimes drowning) in options, enabled (and often forced) to make decisions about things their parents – and certainly their grandparents – had no idea they could make decisions about: where to live, what to do for a living, how many children to have, what religion (or non-religion) to follow This proliferation of choice touches human life at all levels – individuals, families, communities, organizations, national governments. Even global civilization as a whole is faced with the new and disturbing need to make choices about the very future of the planet’s climate. There are many reasons for this; I am inclined to identify scientific/ technological progress and globalization – which is in part the result of it – as the major forces that are carrying us into this astonishingly choice-filled century, this time in which we have infinitely more choices but do not seem to have a choice about whether we have more choices. Today we all live in the whole world, and we all know – in different degrees of course – that there are many ways of living, many ideas and opinions about every subject